On Magnetic Boundary Control for Metric Graphs - Kurasov, P. (Acta Physica Polonica A, 2024)
It is investigated how magnetic boundary control can be used to solve inverse problems for Schrödinger operators on metric graphs. Explicit examples show that such reconstruction is sometimes possible, starting from a single contact vertex in the graph.